Markers for Identifying and Targeting Glioblastoma Cells during Surgery - Schipmann, Stephanie; Schwake, Michael; Suero Molina, Eric; Stummer, Walter (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Glioblastoma is a highly malignant tumor with a poor prognosis. A factor influencing survival that can be affected by the surgeon is the extent of resection (EOR). Due to the infiltrative nature of the tumor, delineation of tumor from normal brain parenchyma is often challenging. To improve EOR and facilitate tumor visualization, several techniques have been developed over the last few years. This literature review presents an overview of current intraoperative strategies for identifying and targeting glioma cells and discusses the benefits and limitations of each technique. Along with conventional techniques such as neuronavigation and ultrasound, fluorescence-guided surgery with different fluorescent agents such as 5-aminolevulinc acid and fluorescein have been widely used. Recently, newer techniques have emerged and are being translated into the operating room, promising delineation of glioblastoma tissue using targeted approaches or identification on a microscopic level, for instance using Raman spectroscopy or confocal microscopy.
Keywords: glioma; interoperative MRI; 5-ALA; fluorescein; indocyanine green